Food Consumption Patterns Based on the Income of Coastal Communities in Pajukukang Village, Bontoa District, Maros Regency - Alfian Adisaputra HY (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the food consumption patterns of coastal communities in Pajukukang Village, Bontoa District, Maros Regency, based on their income levels. Using a mixed-method approach (quantitative and qualitative), the research found that income significantly influences the types and amounts of food consumed. The average household income is Rp 2,750,000 per month, with an average food expenditure of Rp 1,708,333. Fish is the most frequently consumed food, followed by vegetables and snacks, while meat, fruit, and milk consumption is low. Correlation analysis shows a positive relationship between income and food expenditure (r = 0.692). Regression analysis indicates that income accounts for 47.9% of the variability in food expenditure. These results highlight the importance of income in determining food consumption patterns and provide a basis for developing policies to improve food security and nutrition in coastal communities.